Enhancing carbon emission performance in resource-based cities through technological innovation under China’s digital economic development strategy - Wang, Saige; Zhou, Anhua; Zhang, Yue; Yang, Gang; Peng, Xu (Frontiers in Environmental Science, 2024)
As indispensable contributors to the energy and resource sectors, resource-based cities have played a pivotal role in shaping China’s carbon emission landscape. The carbon emission performance of these cities directly impacts the overall carbon footprint of the country, thus highlighting the significance of enhancing carbon emission efficiency within resource-based urban areas to drive nationwide carbon reduction initiatives effectively. The digital economic development strategy presents a promising avenue for improving carbon emission efficiency in resource-based cities. This study employs the super efficiency epsilon-based measure model to assess the carbon emission performance of 103 resource-based cities over the period from 2011 to 2019. Additionally, it utilizes an intermediate effect model to analyse the impact mechanism of digital economic development on carbon emission performance. The findings reveal a substantial 6.3% enhancement in carbon emission performance in resource-based cities attributed to the implementation of the digital development strategy, primarily driven by technological innovation. Furthermore, the study identifies significant dual-threshold effects within economic growth and environmental regulation, shedding light on the complex interplay between these factors. These insights offer valuable guidance for regional carbon reduction endeavors and serve as a valuable supplement to the understanding of the environmental implications of digital economic development in resource-based cities.